IMPACT OF EMERGENCY CESAREAN SECTION ON PRIMIPAROUS WOMEN CONSIDERING SCHEDULED VAGINAL DELIVERY: A QUALITATIVE APPROACH (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Emergency cesarean section (ECS) can be a physically and emotionally challenging experience, particularly for primiparous women who initially plan for a vaginal delivery. The unexpected shift in birth mode can lead to psychological distress, altered postpartum experiences, and changes in future childbirth preferences. Understanding these women's perspectives is essential for improving maternal care and informed decision-making. Objective: To explore the experiences, emotional responses, and perceptions of primiparous women who underwent an ECS despite planning a vaginal delivery. Materials and methods: A Qualitative exploratory study design was conducted over six months in Lahore, Pakistan. Seventeen primiparous women aged 18-35 years who had undergone ESC were recruited using purposive sampling. Participants recruitment continued until data saturation was achieved. Data were collected through semi-structured, in-depth interviews. Interviews were audio-recorded with participant’s consent, transcribed verbatim and anonymized to ensure confidentiality. Data were analyzed manually using Braun and Clarke’s six-phase thematic analysis to identify key themes related to participant’s experiences and future delivery preferences. Results: Seventeen primiparous women participated in the study. Four major themes emerged from the thematic analysis: decision-making surrounding ECS, emotional experiences following ECS, post-cesarean perceptions and social influences, and future delivery considerations. Participants described feelings of fear, disappointment, anxiety and loss of control associated with ECS. Societal expectations and support systems influenced their postpartum experiences and perceptions of childbirth in future pregnancies, concerns regarding safety, recurrence of complications and previous birth experiences continued to shape their preferences and decision-making. Conclusion: ECS had a profound impact on the experiences and future childbirth preferences of primiparous women. Strengthening communication, psychological support and individualized counseling may improve maternal experiences and promote informed decision-making in subsequent pregnancies.